Peran Humas dalam Membentuk Citra LPP: (Studi Kasus di LPP TVRI Yogyakarta) - RELAWATI, DWI KORINA (Program Studi Ilmu Komunikasi FISIP UM Buton, 2024)
For Public Relations (Public Relations) personnel, establishing a new image for TVRI Yogyakarta as an LPP (Public Broadcasting Institution), currently in crisis management, is a challenge in itself that is not easy. Much hope is placed on Public Relations, to be able to see the institution's various potentials, both internal and external, so that they can then be used for the benefit of the institution as much as possible in order to create a new image for TVRI Public. This research aims to determine and analyze the role or activities of Public Relations in the process of imaging TVRI Yogyakarta as an LPP (Public Broadcasting Institution). This research method is descriptive qualitative, using data and fact mining, namely interviews, observation and documentation. The results of the research show that Public Relations of TVRI Yogyakarta realizes the concept of excellent Public Relations by responding more neatly and being involved in various activities related to on and off air. The actualization of the TVRI Yogyakarta television station as an LPP can be assisted by various efforts including the use of social media, collaboration with the local government and various other parties.